Free vibration response of a multilayer smart hybrid composite plate with embedded SMA wires - Malekzadeh,K. (2014)
In this paper, free vibration response of a hybrid composite plate was studied. Effects of some geometrical, physical and material parameters on response of the composite plates embedded with shape memory alloy (SMA) wires were investigated, which have not been reported in the literature thus far. Some of these parameters included important factors affecting free vibration response of the smart hybrid composite plates. The SMA wires were embedded within the layers of the composite laminate. First-order shear deformation theory (FSDT) was utilized to obtain the governing equations of hybrid composite plates. Transverse shear and rotary inertia effects of the plate were taken into consideration. For simply-supported boundary conditions, systematic closed form solutions were obtained by Navier's technique. It was established that dynamic behavior of the smart hybrid composite plate depended on various parameters such as volume fraction, temperature dependent recovery stress and tensile pre-strain of SMA wires and aspect ratio of the laminated hybrid plate.